THE CHANGING DYNAMICS OF THE GLOBAL INTELLECTUAL PROPERTY LEGAL ORDER: EMERGENCE OF A 'NETWORK AGENDA'?. Issue 1 (20th November 2014) - Unknown
Abstract: The Anti-Counterfeiting Trade Agreement (ACTA) had sought to augment intellectual property (IP) enforcement practices, to counter the proliferation of counterfeit and pirate goods and to regulate digital infringements. This paper examines the collapse of ACTA and challenges the traditional orientation of the debate concerning the tension between the 'enforcement' and 'development' agendas. The ACTA negotiating partners, mainly developed states, created a forum outside the aegis of international IP norm-making bodies to avoid the distractions posed by developing countries whilst promoting an alternative 'enforcement agenda'. Despite this effort, ACTA collapsed from 'within'. The paper argues that ACTA failed due to the extemporaneous emergence of a random configuration of civil society groups, academics, 'netizens' and legislators within ACTA negotiating countries independently pursuing an agenda that can be called the 'network agenda'. This new agenda aimed to protect the right to privacy, data protection and freedom of speech within the digital medium. While current debates on the global IP legal order are generally limited to, and characterised by the Global North-South considerations, the 'network agenda' cuts longitudinally through territorial configurations and squarely places the interests of the IP owner against those of the public. Consequently, the paper highlights the potential of the network agenda to dilute the existing polarities in the IP debate and impact on the dynamics of international intellectual property law by creating an inclusive platform within IP discourse that attempts to integrate colliding rationalities present within the world society.